2019
DOI: 10.21608/bfpc.2019.7956.1011
|View full text |Cite
|
Sign up to set email alerts
|

Perception and utilization of complementary and alternative medicine (CAM) among University of Sharjah (UOS) students

Abstract: Background: Complementary and Alternative Medicine (CAM) is a term used for practices and use of products other than conventional standard evidence-based medical care. Objective: To assess the CAM knowledge and utilization among University of Sharjah students, UAE. Method: A cross-sectional survey study was conducted. 250 surveys among UOS students were distributed. The data was obtained through a well-designed questionnaire of 3 main categories. The first part was designed to collect socio-demographic data, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The use of alternative remedies like DDS for the management of diseases in the United Arab Emirates (UAE) as in the Middle East is a widespread practice that has historical, traditional, and religious roots ( Ahmed et al, 2015 ; al Marshedi et al, 2017; AlBraik et al, 2008 , Dha, 2011 , Ibrahim et al, 2019 , Muttappallymyalil et al, 2013 , Sridhar et al, 2017 ). Before the COVID-19 pandemic, studies have estimated the prevalence of DDS use to be between 35% and 39% in the UAE ( Abdulla et al, 2019b , Alhomoud et al, 2016 , Radwan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of alternative remedies like DDS for the management of diseases in the United Arab Emirates (UAE) as in the Middle East is a widespread practice that has historical, traditional, and religious roots ( Ahmed et al, 2015 ; al Marshedi et al, 2017; AlBraik et al, 2008 , Dha, 2011 , Ibrahim et al, 2019 , Muttappallymyalil et al, 2013 , Sridhar et al, 2017 ). Before the COVID-19 pandemic, studies have estimated the prevalence of DDS use to be between 35% and 39% in the UAE ( Abdulla et al, 2019b , Alhomoud et al, 2016 , Radwan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, dental students were found to have little to no knowledge of CAM (30). Positive attitude on T&CM was displayed for study in Saudi Arabia (28), Bangladesh (27), Ghana (25), Canada (31), and the United Arab Emirates (32).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, pharmacy students in Bangladesh mostly used homeopathy, ayurveda, meditation, and massage (27). Cupping was mainly used for University of Sharjah students (32). Notable differences were found for art or music therapy, cupping, hypnosis, prayer or spiritual healing, traditional herbs, and traditional massage.…”
Section: Discussionmentioning
confidence: 99%
“…[11,13] A study conducted at a university in the United Arab Emirates found the rate of TCAM users as 34%, whereas another study from Uganda found that 59% of the participants used TCAM. [14,15] The rate of TCAM use varies from country to country and even in different regions of the same country.…”
Section: As Seen Inmentioning
confidence: 99%
“…Another available study found an association between education and gender variables and TCAM, in which the participants recommended the use of TCAM to others. [14] The research of Mederious found that, out of all socio-demographic variables, only the female gender was an influencing factor,whereas Mwaka et al [15] reported the class of participants as the influencing factor. [27] On the other hand, Samara et al [28] found the class, long-term location of residence and income level effective.…”
Section: As Seen Inmentioning
confidence: 99%